Relationship Between Final-Semester Nursing Students’ Coping Mechanisms and Stress Levels During Competency Exams at Pelamonia Health Science Institute Makassar 2024 (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Stress is a psychological condition that occurs when individuals perceive the demands they face as exceeding their ability to manage or adapt. Final-year students, particularly in health-related fields, are highly vulnerable to stress due to multiple academic responsibilities, including completing coursework, meeting grade targets, writing scientific papers, and preparing for competency examinations. These combined pressures can affect mental health, academic performance, and professional readiness. This study analyzed the relationship between coping mechanisms and stress levels among final-semester students of the Diploma III Nursing Program at the Pelamonia Health Science Institute Makassar in 2024. The research was conducted from August 12 to 24, 2024, involving 31 respondents selected using purposive sampling. Data were collected through standardized questionnaires distributed online via Google Forms. The variables measured included coping mechanisms (adaptive and maladaptive) and stress levels (mild and severe). Data analysis was performed using the Chi-Square statistical test. The results showed that the majority of respondents (83.9%) experienced mild stress, while 16.1% experienced severe stress. Regarding coping strategies, 83.9% of respondents used adaptive coping mechanisms, whereas 16.1% used maladaptive coping mechanisms. The Chi-Square test yielded a p-value of 0.004 (p < 0.05), indicating a significant relationship between coping mechanisms and stress levels. These findings suggest that students who employ adaptive coping strategies tend to experience lower stress levels when facing competency examinations. The results highlight the importance of integrating stress management training and promoting adaptive coping strategies within nursing education programs. Such efforts can help strengthen students’ mental resilience, improve academic performance, and better prepare them for professional practice in the healthcare field.